Production and properties of In and Ir doped Bi1.5Zn0.92Nb1.5O6.92 pyrochlores - (:unkn) unknown (ELSEVIER SCI LTD, 2012)
In and Ir were doped into Bi1.5Zn0.92Nb1.5O6.92 (BZN) pyrochlore using the chemical formulas of Bi1.5Zn0.92-3x/2InxNb1.5O6.92 and Bi1.5Zn0.92Nb1.5-4x/5IrxO6.92. While In was doped into Zn site of BZN, Ir was added into the Nb site. The solubility limits of In and Ir cations in BZN were x=0.1 and x=0.12-0.15, respectively. Above the solubility limits second phases of BiNbO4 and InNbO4 formed for In doping but Bi2Ir2O7 and ZnO phases appeared in Ir doping. SEM investigation confirmed the XRD results. Lattice parameters of BZN pyrochlores slightly increased with In doping but decreased with Ir due to their ionic radii. The dielectric constant of Ir doped BZN slightly decreased with Ir content. However, In doping into the BZN generally decreased the dielectric constant at low doping ratios but increased it at high dopings. Temperature coefficients of Ir and In doped BZN ceramics were significantly affected by doping amount. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: BZN pyrochlore; Doping; Dielectric properties; XRD; DIELECTRIC-PROPERTIES; CRYSTAL-CHEMISTRY; CERAMICS; PHASE